Begum Rokeya: Tale of a Visionary - Quayum, Mohammad Abdul (The Daily Star, Bangladesh, 2012)
An article outlining the life, aspirations and achievements of the Bengali writer, Rokeya Sakhawat Hossain (1880-1932)